2018
DOI: 10.1002/joc.5410
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Pacific Decadal Oscillation on North Central China precipitation during boreal autumn

Abstract: Decadal variations in autumn (September–October–November, SON) precipitation over North Central China since the 1940s are investigated using observations and reanalysis data. They are found to be significantly correlated negatively with the Pacific Decadal Oscillation (PDO). Further analyses indicate that the inter‐decadal changes in SON precipitation over North Central China result from anomaly patterns in the large‐scale atmospheric circulation in the mid‐latitude Northern Hemisphere associated with the PDO.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Before 1999, PDO is the dominant factor. After year 1999, AMO is deemed more relevant to drought in MP, especially in summer [51], supported by a significant Pearson's r in Table S1. Droughts in summer have an adverse impact on vegetation growth, especially in agricultural and pastoral areas, which are totally dependent on natural precipitation.…”
Section: Drought Variations In Different Climatic Regions At the Seasmentioning
confidence: 80%
“…Before 1999, PDO is the dominant factor. After year 1999, AMO is deemed more relevant to drought in MP, especially in summer [51], supported by a significant Pearson's r in Table S1. Droughts in summer have an adverse impact on vegetation growth, especially in agricultural and pastoral areas, which are totally dependent on natural precipitation.…”
Section: Drought Variations In Different Climatic Regions At the Seasmentioning
confidence: 80%
“…Additionally, differences might exist between our results and the results for drought events defined using only precipitation data, which might mostly represent the precipitation conditions during SON (e.g.Gao and Yang, ; Qian and Zhou, ; Qin et al ., ). To further understand these differences, a precipitation index (PI) is constructed using the normalized area‐averaged SON precipitation over North China (PI).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore, drought events will intensify in some areas. Previous studies have revealed that North China, a semiarid region, has experienced severe and prolonged dry periods since the late 1990s (e.g., Zou et al, 2005;Qin et al, 2018). In the study by Wang and Zhai (2003), all of the grades of droughts measured by the "Z" index, which is used by the National Climate Center of China as a tool for the operational real-time monitoring of drought and flood events, showed expanding trends in the main agricultural areas of North China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, numerical simulation based on the downscaling method has also shown that both the SST and the 500-hPa geopotential height can act as prediction factors, considerably improving predictions of autumn precipitation [10]. In addition, other studies have shown that certain oscillation patterns (e.g., the Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO)) can play a crucial role in modulation of regional-scale autumn precipitation over China [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%